2021
DOI: 10.1155/2021/7037786
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Ang2/Tie2 Axis with Tanshinone IIA Elicits Vascular Normalization in Ischemic Injury and Colon Cancer

Abstract: Pathological angiogenesis, as exhibited by aberrant vascular structure and function, has been well deemed to be a hallmark of cancer and various ischemic diseases. Therefore, strategies to normalize vasculature are of potential therapeutic interest in these diseases. Recently, identifying bioactive compounds from medicinal plant extracts to reverse abnormal vasculature has been gaining increasing attention. Tanshinone IIA (Tan IIA), an active component of Salvia miltiorrhiza, has been shown to play significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…It was found that STS inhibited angiogenesis in colon cancer (Zou et al. 2021 ). Moreover, STS was able to attenuate the tumourigenesis of lung cancer (Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that STS inhibited angiogenesis in colon cancer (Zou et al. 2021 ). Moreover, STS was able to attenuate the tumourigenesis of lung cancer (Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…Uniformly, Tan IIA weakened VEGF/HIF-1α expression by controlling the mTOR /p70S6K /RPS6 /4E-BP1 axis in breast cancer ( Li et al, 2015 ). It was of importance that Tan IIA caused vascular stability and vascular normalization via downregulating Ang2-Tie2-AKT-MLCK axis in colon cancer ( Zou et al, 2021 ). The anti-angiogenic properties of tanshinone VI were attributed to its downregulation of adhesion molecules ICAM-1 and VCAM-1 in epithelial cells ( Nicolin et al, 2013 ).…”
Section: The Role Of Ethnopharmacology In Tumor Angiogenesismentioning
confidence: 99%
“…[10][11][12] Tanshinone A (TSA), a diterpenoid compound from Salviae miltiorrhizae radix et rhizoma, has been demonstrated to inhibit the secretion of VEGF and regulate vascular normalisation. [13][14][15][16] Therefore, tumour vessel normalisation through TSA has the potential to increase the abundance of TILs. However, TILs still exhibit insu cient activity.…”
Section: Introductionmentioning
confidence: 99%